THE CHARACTERISTICS OF PROPERTY AND OWNERSHIP IN THE ISLAMIC ECONOMY - Asriadi, Ari; Nasution, M. Yasir; Sugianto, Sugianto (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The concept of property ownership in Islam has unique characteristics, which are in line with human nature. In contrast to the two currently developing concepts, capitalism and communism, neither system has succeeded in bringing individuals or groups into harmony with a social order of life. Individual property rights freedom is the foundation of the concept of capitalism, and the abolition of individual property rights is the main goal of socialism-communism teachings. Because humans are born into the world and do not own any property, the purpose of this paper is to investigate Islam's concept of ownership (the owner of the universe, the role of humans, and who provides everything). This article uses the literature study method, which entails gathering information from various sources, including books and related articles on property ownership in Islam. The findings of this study show that God owns everything in the universe, and humans did not have property in the world at first, but all the gifts that God gave with the guidance to use them as well as possible for the benefit of many people.